Determining the Best Video on Demand Services by Implementing the Analytical Hierarchy Process (AHP) Method and the Multi-Objective Optimization by Ratio Analysis (MOORA) Method - Vivi Asri; Erza Sofian (Peneliti.net, 2023)
The diversity of platforms that provide various types of Video on Demand makes it quite difficult for users to determine the best platform that can be consumed by the public. This research model focuses on selecting from Video on Demand applications that aim to provide alternative recommendations for quality Video on Demand choices for those who are familiar with VoD or not at all. The problem in determining the best Video on Demand service is because each existing Video on Demand has its own unique value or value that makes each platform valuable according to its purpose. The research method here is through a quantitative approach. Data is obtained by conducting direct observations and literature studies, interviews and distributing questionnaires, to 10 respondents who have been validated to have criteria as expert respondents in the field of video on demand technology. The data is then processed by implementing 2 methods with the flow for weighting criteria using the AHP method and ranking alternatives using the MOORA method. The results of the study show that the criteria that are prioritized and influential in choosing a Video on Demand platform are from System Quality with a weight of = 0.45 produced by the platform. Followed by Variants of = 0.29, Price with = 0.15 and Display with weight = 0.11. Then from the ranking results, the alternative chosen based on the calculation is Netflix with an alternative weight = 0.39, then followed by Disney + Hotstar with an alternative weight = 0.34, VIDIO with a weight = 0.29, Viu with = 0.27 and Youtube Premium with an alternative weight = 0.26. So that from the calculation results it can be concluded and recommended to choose Netflix as the best and quality platform